Episomal Nonviral Gene Therapy Vectors Slow Progression of Atherosclerosis in a Model of Familial Hypercholesterolemia - Alastair G Kerr; Lawrence CS Tam; Ashley B Hale; Milena Cioroch; Gillian Douglas; Keith M Channon; Richard Wade-Martins (Molecular Therapy: Nucleic Acids, 2016)
Familial hypercholesterolemia (FH) is a life-threatening genetic disorder characterized by elevated levels of plasma low-density lipoprotein cholesterol (LDL-cholesterol). Current attempts at gene therapy for FH have been limited by the use of strong heterologous promoters which lack genomic DNA elements essential for regulated expression. Here, we have combined a minigene vector expressing the human LDLR cDNA from a 10 kb native human LDLR locus genomic DNA promoter element, with an efficient miRNA targeting 3-hydroxy-3-methylgutaryl-coenzyme A reductase (Hmgcr), to further enhance LDLR expression. We show that the combined vector suppresses endogenous Hmgcr transcripts in vivo, leading to an increase in LDLR transgene expression. In a diet-induced Ldlr-/- mouse model of FH, we show that administration of the combined vector reduces atherogenic plasma lipids by ≃32%. Finally, we demonstrate that our episomal nonviral vectors are able to reduce atherosclerosis by ≃40% after 12 weeks in vivo. Taken together, the vector system we describe exploits the normal cellular regulation of the LDLR to provide prolonged expression of LDLR through targeted knockdown of Hmgcr. This novel gene therapy system could act alone, or in synergy with current therapies that modulate intracellular cholesterol, such as statins, greatly enhancing its therapeutic application for FH.